Newton and the Netherlands How Isaac Newton was Fashioned in the Dutch Republic - Jorink, E.; Maas, A. (Leiden University Press, 2012)
In the course of the eighteenth century, Newton's ideas (in different guises and interpretations) became a veritable hype in Dutch society. In Newton & the Netherlands Newton's sudden success is analyzed in great depth and put into a new perspective.